Personal Hygiene pada Masa Nifas - Fatihatul Hayati (Jurnal Abdimas Kesehatan (JAK), 2020)
ABSTRACT Infection during the puerperium is one of the leading causes of maternal death in developing countries. Puerperal morbidity is an increase in body temperature to 38 ° C or more for 2 days in the first 10 days postpartum, except on the first day. Infections caused by personal hygiene is not good, therefore personal hygiene during the postpartum period of a mother is very important to maintain personal hygiene so as not prone to infection. Maintain overall personal hygiene to avoid infection in both stitches and skin. If a postpartum mother does not perform personal hygiene properly, there can be an infection during the puerperium, namely inflammation caused by the entry of germs into the genetals, effective health education is needed for pregnant women, not only preparation for delivery but also preparation for the period the puerperium, including education about personal hygiene during the puerperium.